The importance of ground temperature to a liquid carbon dioxide pipeline. (August 2015) - Teh, ChiiJyh; Barifcani, Ahmed; Pack, David; Tade, Moses O.
Highlights: The temperature rise due to pumping is less significant than the one due to compression. The cooling requirement at injection site is lower for injecting liquid CO2 . CO2 temperature will decrease regardless of ambient temperatures if buried deep underground. As the elevation increases, a larger pipe size and/or higher delivery pressure will be required. Liquid CO2 has better ability to accommodate the effect of elevation. Abstract: Considerable research and development has been conducted into vary techniques to capture carbon dioxide (CO2 ), including its safe and economical transportation to the storage sites. The CO2 will normally be compressed to the supercritical phase where it demonstrates properties of both liquid and the gas. An alternative for transportation involves the operation solely in the liquid phase. Transporting supercritical CO2 will demand a larger pipe size and consumes more compressor power because its fluid density is lower than the density of liquid CO2 . A significant amount of thermal insulation is also required to maintain the phase and contributes additional cost. This paper firstly model and explore the basic difference between transporting supercritical and liquid CO2, then proposes transporting liquid CO2 with the complete utilization of heat exchange between the ground and CO2 fluid. The pipeline will inevitably face heat exchange between the fluid inside and the surrounding environment due to temperature difference and elevation. In order to avoid phase change, it is necessary to take into account factors such as ambient/soil temperature, soil type, thermal conductivity of pipe and elevation of terrain for ensuring a safe, reliable and cost effective transportation. The models developed in this paper aim to contribute to existing knowledge by highlighting the importance of these factors and laying the foundation for future work when the ambient temperature and elevation changes. A commercially available simulator Aspen HYSYS ® V7.2 in steady state mode, the Peng Robinson Equation of State was used for modelling.